Dependence of the dynamics of changes in the quality of life of patients with bacterial vaginosis on local levels of TNF-α and IL-1β - Grebeniuk, Dmytro; Nazarchuk, Oleksandr; Dzis , Nataliia; Taran, Illia; Slyvka , Elina; Abdullaiev , Vahif; Bobyr , Vitalii; Mashevska , Oksana (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Bacterial vaginosis is among serious health problem for women of reproductive age which influences on their local changes in inflammatory mediators and quality of life. The aim was to assess the dependence of the dynamics of changes in the quality of life of patients with bacterial vaginosis on local levels of TNF-α and IL-1β. Methods: In the prospective study 37 women aged 19-40 years with bacterial vaginosis were treated according to the Centers for Disease Control and Prevention. Patients received vaginal suppositories of clindamycin phosphate (100 mg) once daily for 3 days before bedtime. TNF-α, IL-1β levels in vaginal secretions by means of ELISA test), as well as the quality of life according to the RAND 36-Item Health Survey 1.0 were studied as in control group (once - to determine the reference values) and in the dynamics (the 1st day – before treatment, on the 7th day – after treatment) in the main group. Results: After the treatment microscopy of smears-imprints of vaginal secretions showed the complete absence of pathological microflora. The treatment was well tolerated by all patients. In the result there was proved the role of bacterial vaginosis in a violation of the quality of life of patients mainly due to the mental component of health, even after clinical and laboratory recovery. Conclusions: There was proved the relation of vaginal TNF-α and IL-1β with physical and mental health in patients with bacterial vaginosis which can have a prognostic significance of the disease.